# What is 3c plus 5c plus c simplified?

# Simplify 4.5 plus 25?

The answer is 29.5. Simply add the numbers together arithmetically as you would for the problem two plus two. To check your work, a calculator is the best option.

# 4 plus 3c equals 2 c plus 2 what does c equal?

4 + 3c = 2c + 2 Subtract 4 from each side: 3c = 2c - 2 Subtract 2c from each side: c = -2

# 3c plus 15 over c squared minus 5 plus c over c plus 5?

(3c +15)/(c 2 - 5) + c/(c + 5) = (3c + 15)/(c - 5)(c + 5) + c/(c + 5) = (3c + 15)/(c - 5)(c + 5) + [c (c - 5) /(c + 5) (c - 5) (since the common denominator is (c + 5)(c - 5) = (3c + 15)/(c - 5)(c + 5) + (c 2 - 5c)/(c + 5)(c - 5) = (3c + 15 + c 2 - 5c)/(c - 5)(c + 5) = (c 2 - 2c + 15)/(c -… 5)(c + 5) = [ (c - 5 )(c + 3)]/ (c - 5) (c + 5) (simplify) = (c + 3)/(c + 5) (MORE)

# What is the answer to 17-3c equals 4c plus 3?

What is the question ? Are you looking for the one single value of ' c ' that makes the statement true ? You can find it like this: 17 - 3c = 4c + 3 Add 3c to each side: 17 = 7c + 3 Subtract 3 from each side: 14 = 7c Divide each side by 7: 2 = c

# 3c-12 equals 14 plus 5c?

3c - 12 = 14 + 5c Subtract 3c from each side: -12 = 14 + 2c Subtract 14 from each side: -26 = 2c Divide each side by 2: -13 = c

# Factor 3a plus ab plus 3c plus bc?

a(3+b)+c(3+b) * * * * * This is easy to finish: . . . = (a + c)(3 + b).

# C equals -3 4c plus 5c-2 equals?

When c = -3 then 4c + 5c - 2 = [4 x -3] + [5 x -3] - 2 = -12 +(-15) - 2 = -12 -15 -2 = -29

# What is 4xy plus x3y plus yx2 plus yx plus 3yx simplified?

4xy + x 3 y + yx 2 + yx + 3yx = x 3 y + x 2 y + 8xy = (xy)(x 2 y + x + 8)

# Simplify 0.05x plus 1.02x?

Use the distributive property, ac + bc = (a+b)c; in this case, just add the numbers and place an "x" at the end. This works if the variable or variables (in this case, "x") is the same for both parts.

# How do you Simplify 5n3 plus 7n?

The problem doesn't make sense that you just said. You would have to use algebra. Use the inverses to cross out the variables from each side. Use the ones with like terms first. Then simplify. Calculators help with this type of problem.

# Excluded values of c - 2 over c squared plus 3c?

This is on the multiple choice of my take home test. Its either 0, 2, 0 and -3 or 0,2 and -3 I hope this helps. I was looking for the answer

# How do you simplify 24x2 plus 156x plus 72?

Step 1. Divide by 12: 12(2x 2 + 13x + 6) Step 2. 12(2x +1)(x + 6) Job done

# What is the force exerted on the -4 C by the plus 5C charge?

-4c charge can make the exerted force go on another object such as the 5c positive charge. because wen u multiply em' they make a similarity between them such as -4c+5c which equals to -c or -1c (same thing):)

# Can SOMEBODY solve this equation 19.7 equals 3c plus 7.2 and what c equals?

To answer both of these questions: 1). We're sure somebody can. 2). c = 4 and 1/6 th

# Can someone Simplify the expression 3a plus 2b - c - 2a plus 5b plus 3c by combining like terms?

ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.

# How do you simplify 2x plus 5y -7x plus 2xy?

2x+5y-7x+2xy combine like terms 5y-5x+2xy that's simplified because there are only 3 terms (x, y, and xy) you cannot combine x and y unless it's being multiplied

# How do you simplify 7-2s plus 4 plus 5s?

7-2s+4+5s ..... Okay first you combine like terms(add the like terms)..so its going to be 11+3s I did 7+4=11 then -2s+5s=3s So the answer can be 11+3s or 3s+11

# What is 5c plus 15 equals 30?

5c + 15= 30 - 15 -15 5c = 15 If your solving for just c..... 5c/5 = 30/5 c= 3 Hope this helps adding further your question is incomplete you must ask for thevalue of C, since its a arithmetic equation.

# What is the answer for 3c - 4d equals 6d plus 4c?

3c - 4d = 6d + 4c Subtract 4c from both sides: -c - 4d = 6d Add 4d to both sides: -c = 10d or c = - 10d

# What is the answer to 2a plus b plus 3c equals 2a plus b plus 3c?

That's not even a question. It's only a statement that says that some number is equal to itself.

# What is the like term for 5c plus 2c plus 4b plus 3c?

The like terms are sums of b terms and c terms separately 5c+2c+3c+4b 5c +2c + 4b + 3c => 10c + 4b

# 12 equals 3c-12 plus 5c what is C?

3c - 12 + 5c = 12 Combine the 'c' terms on the left side: 8c - 12 = 12 Add 12 to each side: 8c = 24 Divide each side by 8: c = 3

# How do you simplify 4c2 plus 5c plus 2c?

4c 2 + 5c + 2c = 4c 2 + 7c = c(4c + 7)

# What is -5c plus 9 and how?

You can't tell a thing about -5c+9 until you know what 'c' is. And every time 'c' changes, -5c+9 changes.

# How does 7c plus 3c equals 240?

Collecting like terms together, 10c = 240, therefore, c = 240/10 c is therefore equal to 24.

# How do you simplify 6m plus m plus m plus 4y plus n plus y plus 12 plus 2n?

6m + m + m + 4y + n + y + 12 + 2n Group like terms: 6m + m + m + 2n + n + 4y + y + 12 Add: 8m + 3n + 5y + 12

# Is 4x plus 5c plus 10c-3x equals 0a quadratic equation?

NO,because in quadratic equation highest power of a variable is 2. e.x. 4x 2 -20x+10=0.

# How do you simplify 2a plus 10 plus 5a-2?

2a + 10 + 5a - 2 = (2a + 5a) + (10 - 2) = 7a + 8

# Which is the quotient of 12c5-18c3 plus 9c over -3c?

(12c 5 - 18c 3 + 9c) / (-3c) = -4c 4 + 6c 2 - 3

# How do you simplify 6x plus x?

Perform the addition. You know that 6 cows plus one cow is 7 cows, 6 kittens plus 1 kitten is 7 kittens, and 6 computers plus 1 computer is 7 computers. It should not surprise you to discover that [ 6x + 1x ] = 7x .

# How do you simplify i plus 6i?

answer is 7i, since its the same thing as: i + (i + i + i + i + i +i)

# What is the answer to 20c plus 5 equals 5c plus 65?

20c + 5 = 5c + 65 Divide through by 5: 4c + 1 = c + 13 Subtract c from both sides: 3c + 1 = 13 Subtract 1 from both sides: 3c = 12 Divide both sides by 3: c = 4 20c + 5 = 5c +65 20c - 5c= 65 - 5.
15c = 60.
15c/15 = 60/15.
c = 4 (alternative method).

# How do you solve this 7c plus 2 plus 3c?

It equals 10c+2 because you have to combine like terms when you use variables. So since there is a 7c and a 3c you add those because it says plus add you end up with 10c+2 because you are still adding the 2.

# What is 2c plus 4-3c equals -9 plus c plus 5?

2c + 4 - 3c = -9 + c + 5 -c + 4 = c - 4 -2c = -8 2c = 8 c = 4

# How do you simplify 5x plus x?

The simplified answer would be 6x. In this case, x=1. So, you would add 1 to the 5, making is 6x

# What is the sum of 21 equals 3c plus 6?

The solution (not sum) to the equation 21 = 3c + 6 is as follows: 21 = 3c + 6 21 - 6 = 3c + 6 - 6 15 = 3c 3c = 15 3c/3 = 21/3 c = 7

# What is 8y plus 9 plus 7y simplified?

8y + 7y = 15y So [ 8y + 9 + 7y ] = 15y + 9 If you want to get fancy and factor that expression, it's 3(5y + 3) .

# How do you sovle 3c plus 5 equals c plus 15?

It is:- 3c+5 = c+15 Subtact 5 and c from both sides: 2c = 10 Divide both sides by 2 to find the value of c: c = 5

# How do you simplify 4i2 plus 4i7?

4i 2 + 4i 7 All I can see is factoring out a 4i 2 4i 2 (1 + i 5 ) ====

# What is 4a plus 3c-2b-c plus a-b?

4a + 3c - 2b - c + a - b = 5a - 3b + 2c

# What is the answer of 8 plus 3c equals 3c?

This is impossible because if each side has to equal each other, the left side will always be eight more than the other

# What is -7 equals -3c plus 93?

Doing it step by step: -7 = -3c + 93 3c = 7 + 93 3c = 100 c= 33 1/3

# How do you use the distributive property to simplify the expression c plus 0.06c?

c + 0.06c = 1c + 0.06c = c*(1 + 0.06) = c*1.06 which is more conventionally written as 1.06c.

# What is the answer for 5c plus 7 equals 23?

5c+7=23 -7 -7 5c=16 /5 /5 c= 3 & 1/5 or 16/5 thats really easy algebra 1 homework isn't it

# What is the 3 coefficient of 5c plus 7m?

5 and 7 are two coefficient. And that is all. There is no third coefficient.

# What is -5c plus d equals 2c?

It is a single equation of direct proportionality. It cannot be solved since that would require two linear equations.

# How do you simplify 25 plus 810?

25 + 810 = 835. You seem to be unaware of the fact that you could have obtained the answer much more easily and quickly by using the calculator that comes as part of your computer.

# Is -1 -1 a solution of y 3c plus 2?

If you mean: y = 3x+2 then (-1, -1) will satisfy the straight line equation

# Simplify 24 plus 17?

24 + 17 = 41 2/4 + 1/7 = 14/28 + 4/28 = 18/28 = 9/14

# 8a - 2b plus 3c?

That may be, but a single linear equation in three unknown variables cannot be solved.